Design and characterization of a chimeric alginate lyase for immobilization to produce well‐defined oligosaccharides. Issue 2 (8th June 2022) - Zhang, Hongxiu; Lyu, Qianqian; Liu, Xiaohua; Liu, Weizhi
Abstract: Recently, a novel two‐domain alginate lyase (AlyAL01) was cloned from Algibacter sp. and successfully overexpressed in Escherichia coli BL21(DE3). Biochemical analysis showed that the N‐terminal carbohydrate‐binding module (CBM) of AlyAL01 had no effect on the enzyme activity and product distributions. Therefore, the N‐terminal CBM was substituted with CBM3 to confer the designed chimeric protein with the ability to specifically bind to regenerated amorphous cellulose. As anticipated, the designed chimeric protein (CBM3‐L1) exhibited a similar enzyme activity. Moreover, it was found that the CBM3‐L1 combined the purification and immobilization in one step with high immobilized efficiency of 65.8%. The immobilized enzyme exhibited good storage stability and moderate reusability. The immobilized enzyme could keep 85% activity when incubated at 4°C for 60 days and 70% activity when incubated at 25°C for 30 days. Furthermore, the immobilized CBM3‐L1 kept about 50% of its initial activity after being reused five times. Finally, immobilized CBM3‐L1 successively produced well‐defined alginate oligosaccharides (AOS) with DPs of 2–6 by controlling reaction time. In sum, our current study provided a feasible strategy for well‐defined AOS production. Abstract : The chimeric alginate lyase with cellulose‐binding domain was immobilized onto regenerated amorphous cellulose. The immobilized enzyme exhibited good storage stability and moderate reusability. Meanwhile, the immobilized enzyme produced alginate oligosaccharides with a stable composition, which provided a feasible strategy for well‐defined alginate oligosaccharide production.